Interpersonal Communication Between Young Couples In North Jakarta In Dealing With Financial Problems - Tarisa Putri; Nurlina Rahman; Wininda Qusnul Khotimah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to explain the form of interpersonal communication in the relationship of young couples facing financial problems, and its impact on household harmony. The main focus of this study is to understand the communication patterns formed between couples when they are faced with financial pressure in their household life. This study uses a qualitative approach with an in-depth interview method with four young couples living in North Jakarta who are experiencing financial problems. This study refers to the theory of interpersonal relationships and the concept of interpersonal communication that emphasizes openness, empathy, equality, and emotional support in establishing healthy relationships. In addition, this study also places communication in a relational context, where every interaction between husband and wife has an influence on the emotional dynamics and stability of the relationship. Data analysis was conducted using the Miles and Huberman interactive model. The results of the study indicate that communication that is carried out openly, supports each other, and is able to manage emotions positively has a great influence on maintaining household harmony even under economic pressure. Conversely, dominant or closed communication patterns actually increase the potential for conflict. Thus, healthy interpersonal communication is an important factor in building resilience in young couples' relationships amidst financial problems.